INFRASTRUCTURE PROJECTS: FORECAST ERRORS, UNCERTANTIES AND RISKS - Alexander E. Lantsov (Статистика и экономика)
Due to capital intensiveness of infrastructure projects, public budget deﬁ cits, and lack of private funds available it’s highly important to evaluate the future capitalcosts and return of infrastructure projectsaccurately to increase provision of economy with infrastructure assets.The article considers typical errors inforecasting return of infrastructure projectsand capital expenditures to develop it, riskclassiﬁcation and measures to mitigate it.